Related studies on measuring the normal values of optic nerve sheath diameter in healthy Chinese adults based on CT scans - Lei Han; Ning Su; Chao Wu; Jiamin Yang; Xiaolin Liu (Scientific Reports)
Abstract To measure the normal reference value of optic nerve sheath diameter (ONSD) and its correlation with eyeball transverse diameter (ETD), age and sex in Chinese adults by CT. The data of healthy adults who underwent head scan in Baotou Central Hospital from March 2022 to May 2023 were retrospectively collected. The ETD of both eyes and the ONSD (ONSD3mm, ONSD10mm) at 3 mm and 10 mm behind the eyeball were measured, and the relationship between ONSD and age, sex and ETD was analyzed by linear regression. A total of 360 subjects were included, 180 males and 180 females, aged 48.5 (33.00, 63.00) years. The average ONSD3mm, 10 mm and ETD of 360 included subjects were 5.28 (95% CI 5.23–5.32) mm, 4.34 (95% CI 4.30–4.37) mm and 22.47 (95% CI 22.38–22.56) mm, respectively. Univariate linear regression analysis showed that gender (P < 0.001) and ETD (P < 0.001) were the influencing factors of the mean ONSD. Further multivariate linear regression analysis also showed that gender (P < 0.001) and ETD (P < 0.01) were associated with ONSD values. The comparison of parameters between different genders showed that the values of all parameters in males were greater than those in females, and the difference between the two groups was statistically significant (P < 0.001). In addition, we further measured the ONSD/ETD values, which averaged 0.24 (0.23–0.24) at 3 mm and 0.19 (0.19–0.20) at 10 mm. The average ONSD3mm, 10 mm and ETD of healthy Chinese adults were 5.28 (95% CI 5.23–5.32) mm, 4.34 (95% CI 4.30–4.37) mm and 22.47 (95% CI 22.38–22.56) mm, respectively. At the same time, it is found that gender and ETD are the influencing factors of ONSD, and the diameter of ONSD is different between men and women.